A Review of Analytical Methods for Quantitative Determination and Validation of Fluvoxamine: Review Article (Journal of Pharma Insights and Research, 2025)
Fluvoxamine, a potent selective serotonin reuptake inhibitor, necessitates robust analytical methodologies for accurate quantification in pharmaceutical formulations and biological matrices. This review presents current analytical methods developed for the determination of fluvoxamine, emphasizing method validation and application in quality control processes. Ultraviolet spectrophotometry has demonstrated reliable quantification at wavelengths between 230-246 nm, with linear responses in the range of 2-30 µg/mL. Advanced chromatographic techniques, particularly RP-HPLC methods utilizing C18 columns and varied mobile phase compositions, have achieved superior separation with detection limits as low as 0.394 µg/mL. Stability-indicating assays have revealed fluvoxamine's susceptibility to degradation under acidic, basic, and oxidative conditions. Spectrofluorometric methods have shown exceptional sensitivity, detecting concentrations as low as 0.01 µg/mL in biological fluids. Novel approaches incorporating green chemistry principles have emerged, utilizing environmentally friendly solvents while maintaining analytical precision. Method validation studies consistently demonstrate excellent linearity (r² > 0.999), precision (RSD < 2%), and accuracy (recovery 97-102%). These methodologies have proven instrumental in pharmaceutical quality control, enabling precise quantification in both bulk drug substance and finished dosage forms.